The novel Lyme borreliosis vaccine VLA15 shows broad protection against Borrelia species expressing six different OspA serotypes - Comstedt, Pär; Schüler, Wolfgang; Meinke, Andreas; Lundberg, Urban (PLOS ONE, 2017)
We have previously shown that the Outer surface protein A (OspA) based Lyme borreliosis vaccine VLA15 induces protective immunity in mice. Herein, we report the induction of protective immunity by VLA15 with mouse models using ticks infected with B. burgdorferi (OspA serotype 1), B. afzelii (OspA serotype 2) and B. bavariensis (OspA serotype 4) or with in vitro grown B. garinii (OspA serotype 5 and 6) for challenge. For B. garinii (OspA serotype 3), we have developed a growth inhibition assay using chicken complement and functional antibodies targeting B. garinii (OspA serotype 3) could be demonstrated after immunization with VLA15. Furthermore, following three priming immunizations, a booster dose was administered five months later and the induction of immunological memory could be confirmed. Thus, the antibody titers after the booster dose were increased considerably compared to those after primary immunization. In addition, the half-lives of anti-OspA serotype specific antibodies after administration of the booster immunization were longer than after primary immunization. Taken together, we could show that VLA15 induced protection in mice against challenge with four different clinically relevant Borrelia species (B. burgdorferi, B. afzelii, B. garinii and B. bavariensis) expressing five of the six OspA serotypes included in the vaccine. The protection data is supported by functional assays showing efficacy against spirochetes expressing any of the six OspA serotypes (1 to 6). To our knowledge, this is the first time a Lyme borreliosis vaccine has been able to demonstrate such broad protection in preclinical studies. These new data provide further promise for the clinical development of VLA15 and supports our efforts to provide a new Lyme borreliosis vaccine available for global use.